Requests and apologies in two languages among bilingual speakers: A comparison of heritage English speakers and English- and Hebrew-dominant bilinguals - Bar On, Sagit; Meir, Natalia (Frontiers in Psychology, 2022)
Introduction Linguistic research over the last two decades has uncovered a significant number of properties that identify heritage language (HL) speakers as a particular phenomenon within bilingualism. However, despite the rapid development of HL research, the sphere of HL speech act pragmatics is still in its infancy. Methodology The current study sought to cover part of this gap by investigating both languages of HL adult speakers for whom English is their HL and Hebrew is their dominant societal language (SL; n = 20, hereafter HS) in comparison with two other groups: Hebrew-dominant speakers who were born to Hebrew-speaking families and raised in Israel, and thus English is the language of their schooling (n = 20, hereafter HEB-D), and English-dominant speakers who were born to English-speaking families and immigrated to Israel from an English-speaking country after the age of 18, and thus Hebrew is their L2 (n = 20, hereafter ENG-D). The discourse-pragmatic tasks in English and in Hebrew consisted of the same 36 scenarios eliciting requests and apologies in each language. Each request was followed by an apology that is related. Results The results indicated that Hebrew-dominant speakers and English-dominant speakers, i.e., HEB-D and ENG-D, had different strategies for the realization of requests and apologies which they systematically transferred from their dominant language into their weaker one, confirming the cross-cultural and cross-linguistic differences between request and apology realizations in English and in Hebrew. However, the picture was more complex for the HL speakers in their HL-English and SL-Hebrew as in some cases their strategies paired up with the ENG-D in English, and with the HEB-D in Hebrew, while in other cases they developed a unique and hybrid linguistic style reflecting the strategies of both languages. Discussion The investigation of both languages of HL speakers enabled us to compare features of the two linguistic systems and make conclusions about their nature.